Artificial ventilation during transport: A randomized crossover study of manual resuscitators with comparison to mechanical ventilators in a simulation model. Issue 9 (2nd September 2018) - Lucy, Malcolm J.; Gamble, Jonathan J.; Peeling, Andrew; Lam, Jimmy T.H.; Balbuena, Lloyd
Abstract: Background: Positive‐pressure ventilation in critically ill patients is commonly administered via a manual resuscitation device or a mechanical ventilator during transport. Our group previously compared delivered ventilation parameters between a self‐inflating resuscitator and a flow‐inflating resuscitator during simulated in‐hospital pediatric transport.1 However, unequal group access to inline pressure manometry may have biased our results. In this study, we examined the performance of the self‐inflating resuscitator and the flow‐inflating resuscitator, both equipped with inline manometry, and several mechanical ventilators to deliver prescribed ventilation parameters during simulated pediatric transport. Methods: Thirty anesthesia providers were randomized to initial resuscitator device used to hand ventilate a test lung. The resuscitators studied were a Jackson‐Rees circuit (flow‐inflating resuscitator) or a Laerdal pediatric silicone resuscitator (self‐inflating resuscitator), both employing manometers. The scenario was repeated using several mechanical transport ventilators (Hamilton‐T1, LTV ® 1000, and LTV ® 1200). The primary outcome was the proportion of total breaths delivered within the predefined target PIP/PEEP range (30 ± 3, 10 ± 3 cm H2 O). Results: The Hamilton‐T1 outperformed the other ventilators for breaths in the recommended range (χ 2 = 2284, df = 2, P < .001) and with no breaths in the unacceptable range (χ 2 = 2333, df = 2, P < .001). Hamilton‐T1 also outperformed all human providers in proportion of delivered acceptable and unacceptable breaths (χ 2 = 4540, df = 3, P < .001 and χ 2 = 639, df = 3, P < .001, respectively). Compared with the flow‐inflating resuscitator, the self‐inflating resuscitator was associated with greater odds of breaths falling outside the recommended range (Odds ratio (95% CI): 1.81 (1.51‐2.17)) or unacceptable (Odds ratio (95% CI): 1.63 (1.48‐1.81)). Conclusion: This study demonstrates that a majority of breaths delivered by manual resuscitation device fall outside of target range regardless of provider experience or device type. The mechanical ventilator (Hamilton‐T1) outperforms the other positive‐pressure ventilation methods with respect to delivery of important ventilation parameters. In contrast, 100% of breaths delivered by the LTV 1200 were deemed unacceptable.